Synthesis of Phased Cylindrical Arc Antenna Arrays - Hussein Rammal; Charif Olleik; Kamal Sabbah; Mohammad Rammal; Patrick Vaudon (International Journal of Antennas and Propagation)
This paper describes a new approach to synthesize cylindrical antenna arrays controlled by the phase excitation, to synthesize directive lobe and multilobe patterns with steered zero. The proposed method is based on iterative minimization of a function that incorporates constraints imposed in each direction. An 8-element cylindrical antenna has been simulated and tested for various types of beam configurations.